The Effect of Short Term Supplementation with Curcumin on Superoxide Dismutase, Glutathione Redoctase, Glutathione Peroxidase and Catalase Serum in Basketball Players - farah nameni; maasumeh nurani pilehrud; mahsa mohsenzadeh; fariba aghaii (Fasa University of Medical Sciences, 2019)
Background & Objective: Curcumin has antioxidants effects and strong anti-inflammatory properties and has a protective and therapeutic roll. This combination can be effective in reducing inflammation and increases reactive oxygen species (ROS) in the skeletal muscle and blood. This study aimed at investigating the effect of supplementation with curcumin on antioxidants enzymes after a basketball intensive training session in girls. Materials & Methods: For this purpose 30 female basketball players are divided into 2 homogeneous supplement and placebo groups. Oral curcumin was used for a period of 14 days,3 time a day in the amount of 1200 mg by the supplement and placebo groups. After 14 days of supplementation, all subjects participated in the basketball acute training protocol. Blood samples were collected and used for determination of antioxidant enzymes activity on base, after supplementation and after exercise training. Differences between the placebo and curcumin groups were analyzed by analysis of variance (ANOVA) repeated measures test and Bonferroni test was used for post hoc multiple comparisons among means. Results: Mean± SD showed all antioxidant enzymes increased but ANOVA repeated measures results showed that GPX and SOD activity (U/mg pro) in supplemental group was increased significantly (P=0.05); Whereas, CAT and GR activity (U/mg pro) were not significantly different. Conclusion: These findings showed that curcumin consumption before one bout acute training may affect antioxidant enzymes concentration and promotes antioxidant capacity of adolescent athletes during heavy competitions. This strategy can accelerate recovery from repeated stress. Curcumin increased antioxidant activities.